(untitled) (International Journal of Environmental Sciences, 2025)
Drosophila melanogaster is increasingly utilized as a versatile and most potent model genetic organism as an alternative to rodent and C. elegans models to study human diseases including metabolic disorder like diabetes. There are seven insulin–like peptides in insulin signaling pathway of Drosophila melanogaster and is very similar to the human insulin pathway to study different aspects of the diabetic status. In this study we discuss features of metabolic syndrome, and related abnormalities including insulin resistance and metabolic disorders. This study will focus on the diet-dependent development of metabolic disorder in fruit flies by feeding them with high sugar diet (HSD). Furthermore, regular observation of morphogenetic changes pertaining to weight, locomotor gait, memory, longevity, and insulin signaling pathways etc., additionally intended to observe the antidiabetic effects of food additives such as powder of Cinnamomum cassia on the diabetic larvae. The study also evaluates the potential antidiabetic effect of the food additive Cinnamomum cassia, known for its bioactive compound cinnamaldehyde. Imbalanced diet disrupts metabolism, homeostasis in Drosophila melanogaster and promotes insulin- resistant phenotypes. Therefore, the fly system may be a useful alternative tool in the exploration of molecular mechanisms of insulin resistance and the development of pharmacologic treatments. This study focuses on identifying epigenetic changes in insulin/insulin-like growth factor (IIS) which is required for both energy metabolism and growth of larval tissues and to understand regulatory mechanism of the genes Drosophila insulin like peptides (DILP- 1 to DILP- 8) expressed in the brain of Drosophila. In Drosophila growth and metabolism is mediated by these DILPs. This study analyzes metabolic disorder, alteration in insulin signaling pathway, antidiabetic effects of food additives and disease intervention.